Securitization of human rights North Korean refugees in East Asia - Kim, Mikyoung (Santa Barbara, California Praeger, 2012)
"This important book focuses on North Korean refugee human rights issues--a topic largely ignored in favor of addressing North Korea's domestic politics and deterrence of Pyongyang's nuclear threat"
Includes bibliographical references and index.
Keywords: Human rights -- Korea (North); Korea (North) -- Politics and government; Korea (North) -- Foreign relations